Enhancing Islamic Religious Education Through Religious Moderation: Insights from Yudharta University-Pasuruan - Maftuh Maftuh; Medy Elliya Devita (SYAMIL: Journal of Islamic Education, 2023)
The development of Islamic Religious Education (PAI) curriculum with the insight of religious moderation is one of the strategic efforts to face the challenges of pluralism in higher education, especially at Yudharta University Pasuruan which is a public university. This study aims to formulate a model of PAI curriculum that integrates religious moderation values. The research method used is field-research with a qualitative-descriptive approach. Data were obtained through interviews, observations, and documentation studies involving lecturers, students, and managers of PAI study programs at Yudharta University. The results showed that the development of a curriculum with a religious moderation insight was implemented The curriculum development model used at the Yudharta campus uses and applies the MBKM model, because indeed the spirit of MBKM is a form of implementation of Merdeka Belajar, where Merdeka here is to give freedom to students. The forms of implementation applied at the Yudharta campus include strengthening moderation values through both academic and non-academic activities, including lectures, discussions and workshops involving many parties from different religious backgrounds.